Knowledge of School-Going Adolescents About the Oral Effects of Tobacco Usage in Ibadan, Southwest Nigeria (2020)
The individual knowledge of the effects of tobacco usage on health plays an important role in its uptake. Tobacco consumption usually starts during adolescence, and lack of knowledge about the oral problems of tobacco usage probably plays a role in it. To determine the knowledge of adolescents about the effect of tobacco usage on oral health. A cross-sectional study was conducted among 1,465 adolescents aged 12 to 20 years who attended senior secondary schools in a major city in Nigeria. Data were obtained through a semistructured questionnaire. Data obtained were analyzed with SPSS. The mean age of respondents was 15.2 (_1.4) years. Only 40 (2.7%) of them used tobacco at the time of study and 992 (67.7%) said that tobacco usage has effect(s) on oral health. The main effects mentioned were mouth odor: 338 (34.1%); teethdiscoloration: 297 (29.9%); tooth decay: 138 (13.9%); damage to teeth: 72 (7.3%); lip discoloration: 39 (3.9%); and oral cancer: 11 (1.1%). It was found that female respondents (72.1%, odds ratio¼1.4, confidence interval¼1.1–1.7, p¼.005); those aged 12 to 15 years (73.6%, odds ratio¼2.0, confidence interval¼1.6–2.5, p<.001); and children of skilled workers (73.4%, odds ratio¼1.9, confidence interval¼1.2–3.0, p¼.008) were more likely to mention that tobacco has adverse effect(s) on oral health. Although two thirds of the students knew that tobacco usage has effects on oral health, there were gross inadequaciesin the knowledge and misconceptions about those effects